Concise Japanese dictionary Japanese-English English-Japanese - Martin, Samuel E. (Samuel Elmo) 1924-2009; Khan, Sayaka; Perry, Fred Thomas (Tuttle, 2012)
Tuttle Concise Japanese Dictionary, now with 30% more content, is a completely updated dictionary designed for students and business people who are living in Japan and using the Japanese language on a daily basis. Its greatest advantage is that it contains recent idiomatic expressions which have become popular in the past several years and which are not found in other competing dictionaries